Implementasi Nilai-Nilai Budaya Lokal Dalam Kerajinan Tenun Melalui Pembelajaran IPAS Di Sekolah Dasar - Bahri, Muh.; Waluyo, Edy; Halqi, Muhammad (Universitas Hamzanwadi, 2024)
This study aims to: 1) find cultural values ​​in Pringgasela woven cloth crafts, Pringgasela District, East Lombok Regency; 2) explain the role and function of cultural values ​​in Pringgasela woven cloth crafts, Pringgasela District, East Lombok Regency, and 3) reflect the implementation of cultural values ​​in Pringgasela woven cloth crafts through learning natural and social sciences (IPAS) in Elementary Schools. This study uses a qualitative approach to find local cultural values ​​in woven fabric crafts. The study was conducted at Pringgasela Elementary School with research subjects of community leaders, weavers, and teachers. Data collection techniques used observation, interviews, and documentation. Test the validity of the data with examination steps, namely the degree of trust, transferability, dependence, and certainty. The analysis stages consist of data collection, data reduction, data presentation, drawing conclusions. The results of the study show that: 1) cultural values ​​in woven fabric crafts are related to self, fellow human beings, and the environment. Values ​​related to self are five values, namely creative values, self-confidence, hard work, perseverance, and patience. Cultural values ​​related to fellow human beings are five values, namely the values ​​of cooperation, caring for others, simplicity, entrepreneurship, and precision. Cultural values ​​related to the environment are four values, namely the values ​​of mutual cooperation, commitment, caring for the environment, and responsibility; 2) the role of cultural values ​​in woven fabric crafts, namely preserving identity, a container for economic development, strengthening social relations, cultural heritage. The function of cultural values ​​in woven fabric crafts as a symbol of culture, strengthening social, economic relations, and a reflection of identity, and 3) implementation of cultural values ​​in woven fabric crafts through science and natural science learning in elementary schools is carried out through classroom activities, science and natural science learning themes, and learning methods. Classroom activities consist of additional study hours, strengthening local cultural appreciation, and shaping student character. The science and natural science learning theme in elementary schools related to woven fabric crafts is developed through the materials